Correlation Between The Waiting Time And Anxiety Levels Of The Individuals During Venipuncture Before (Journal of Namibian Studies : History Politics Culture, 2023)
Even though it's necessary for both diagnosis and treatment, venipuncture may cause discomfort and anxiety in adults. From November 2020 to December 2020, researchers at a training and research hospital ran a descriptive and cross-sectional study in their adult blood collection unit. Data was collected using the Visual Analog Scale (VAS), Spielberg State-Trait Anxiety Inventory (STAI), and the Case Report Form. Evaluation of the data was done using descriptive statistics, the Mann-Whitney U Test, the Kruskal-Wallis Test, the Post Hoc Dunn test with Bonferroni Correction, and the Spearman Correlation Coefficient. A grand number of 140 willing blood donors were chosen for this investigation. A median of 6.0 (0.0-62.0) minutes was spent waiting for the operation to begin. The participants reported more discomfort during the venipuncture as the time to provide blood rose, but no change in their anxiety levels.